Pengembangan Mesh Network Sebagai Ekspansi Protokol LoRaWAN di Politeknik Negeri Malang - Noprianto Noprianto; Reynaldi Fakhri Pratama; Habibie Ed Dien; Muhammad Hasyim Ratsanjani; Muhammad Afif Hendrawan (Jurnal Teknologi Informasi dan Multimedia, 2024)
In realizing a smart campus, Politeknik Negeri Malang (Polinema) has implemented digital technology in its learning and administrative processes with the goal of improving efficiency, speed, and operational ease. One of the key areas being developed is the Internet of Things (IoT), which is expected to function autonomously to support various campus activities. However, the main challenges in IoT implementation are the limitations in communication range and device power consumption, which cause issues in sensor and actuator data transmission, especially when data cannot be optimally received between nodes. To address these challenges, Polinema is ex-ploring the application of LoRaWAN technology. Although LoRaWAN is effective, it experiences a decline in data transmission quality when the sender and receiver are located in multi-story buildings, which can lead to delays, packet loss, or other disruptions. As a solution, the use of a Mesh Network is proposed to enhance the range and stability of data transmission. This study collected data using RSSI, SNR, and delay parameters in the civil engineering building at Polinema, with sensor data visualized through Grafana. The results show that the system can be well-integrated without conflicts between WiFi and LoRa. The average transmission time was approximately 29 seconds, with no packet loss detected. Additionally, changing the transmission method to confirmed uplink was necessary to maintain data integrity, while adjusting transmis-sion intervals was crucial to avoid scheduling issues. These findings indicate that implementing a Mesh Network as an extension of the LoRaWAN protocol can significantly improve the perfor-mance of IoT systems in Polinema’s indoor environment.